DAMPAK TIDAK DIBERIKAN IMUNISASI CAMPAK PADA BALITA TERHADAP KEJADIAN PENYAKIT CAMPAK DI DESA BINDANG KECAMATANPASEAN KABUPATEN PAMEKASAN - Dewi Yanti, Ariu; Hadiyana, Ria (JURNAL KEPERAWATAN BINA SEHAT, 2016)
Measles immunization that gets more attention. This is related to the reality that measles is one of the leading causes of death on children. Immunization is vital for safety of the children from various diseases that threaten. Immunization is a must for parents preparing ther children grow up healthy and intelligent. The purpose of this study was to find out impact of children who is not measles immunized on incidence of measles. The design of studi is Descriptif with approach Cross Sectional. The population is mohers who have children not measles immunized as many as 108 people to obtain as many as 48 samples were taken with purposive sampling. The variable is impact of children who is not measles immunized on incidence of measles in Bindang Pasean Pamekasan. The data was taken by using a questionnaire. After having collected the data and do analyze data. The result of study showed that from 48 children, 27 children (56,2%) ever measles and 21 children (43,8%) never measles. The result analyze data show that there is impact of children who is not measles immunized on incidence of measles. children who are not immunized measles the risk for measles than children who get immunized. Further efforts to protect children from measles is to provide measles immunization at the age of 9 months.Keyword : measles immunization, children, incidence of measles